Influence of human papillomavirus infection on the vaginal microbiome of women with immunocompetency - Rebouças, Karinne Cisne Fernandes; Eleutério Junior, José; Eleutério, Renata Mírian Nunes; Augusto, Kathiane Lustosa; Leopoldo, Karla Maria Rêgo (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The influence of vaginal infections on the natural history of human papillomavirus (HPV) is still unclear. Objective: To determine if patients with low-grade squamous intraepithelial lesions (LSILs) and HPV have more vulvovaginitis than patients with normal liquid-based cervical cytology who were negative for HPV. Methods: This is a cross-sectional study including 322 patients who underwent cervical exams. One hundred and sixty-seven of these patients had LSILs on cervical cytology and were simultaneously hybrid capture 2 (HC2)-positive for HPV, and the remaining 155 patients were negative for malignancies and intraepithelial lesions by cytology and HC2-negative for HPV. The prevalence of vaginal infections in both groups was compared using the χ2 test without Yates’ correction. Results: Among the patients with HPV and LSILs, the most common vaginal infection was vaginosis (8.98%) compared to candidiasis (12.9%) in the patients without LSILs and HPV. No significant differences were found in the prevalence of vaginosis between the two groups (p=0.53). Candidiasis was statistically more prevalent in patients without LSILs and HPV (p<0.001). Conclusion: An association was found between the presence of Candida and the absence of HPV. Although vaginosis was more frequent among patients with LSILs and HPV, it was not statistically significant.